Spatiotemporal Distribution of Nitrous Oxide on the Northeastern Bering Sea Shelf - Jiexia Zhang; Liyang Zhan; Liqi Chen; Haiyan Jin; Man Wu; Wangwang Ye; Jian Liu (Water, 2022)
Rapid warming and loss of sea ice in the Arctic Ocean could play an important role in the dissolution and emission of greenhouse gas nitrous oxide (N2O). We investigated dissolved N2O in spatiotemporal distribution on the northeastern Bering Sea shelf (NEBS) in the summer of 2012. The results showed that N2O concentrations were higher in the Chirikov Basin (mean ± SD, 14.8 ± 2.4 nmol/L) than in the south of St. Lawrence Island (mean ± SD, 17.7 ± 2.3 nmol/L). In the Chirikov Basin, N2O displayed a decreasing distribution pattern from west (~20.4 nmol/L) to east (~12.9 nmol/L). In the area south of St. Lawrence Island, N2O almost presented a two-layer structure, although it showed a vertically homogeneous distribution in the inner shelf. In the cold bottom water, the N2O was affected mainly by in situ production or sediment emission. Longer resident time may cause N2O accumulation in the cold bottom water. The calculated sea–air flux (−1.6~36.2 μmol/(m2·d)) indicates that the NEBS is an important potential source of atmospheric N2O and could play an important role in global oceanic N2O emission with intensifying global issues.